Особливості фотосинтетичної діяльності гібридів соняшнику (Helianthus annuus L.) (F1) залежно від дії регулятора росту рослин в умовах Південного Степу України - Єременко, Оксана Анатоліївна; Yeremenko, Oksana (Херсон : ХДАУ, Грінь Д. С., 2017)
UA: Наведено результати досліджень впливу регулятора росту рослин АКМ на фотосинтетичну діяльність гібридів соняшнику за умов недостатнього зволоження Південного Степу України. Встановлено, що передпосівна обробка насіння соняшнику регулятором росту рослин обумовлює збільшення площі листкової поверхні на 19 %. В середньому за роки досліджень у фазу цвітіння в листках контрольних рослин гібриду Персей містилося 8,98 мг/г сухої речовини хлорофілів, що відповідно на 31 % більше, ніж у гібридів Альфа та Логос. Встановлено, що максимальний вплив на індекс пігментів (Хл./кар.) мав фактор А (58,8%), тоді як частка впливу факторів В и С дорівнювала 1,2 та 1,8 відповідно. Також сильною виявилась і взаємодія факторів А та С (24,0 %). Регулятор росту рослин АКМ підвищує стійкість рослин соняшнику до абіотичних стресів та збільшує врожайність у середньому на 31,8 % у порівнянні з контролем. EN: The results of the research on the influence of the AKM plant growth regulator on the photosynthetic activity of sunflower hybrids under the conditions of insufficient humidification of the Southern Steppe of Ukraine are presented. It has been established that pre-sowing treatment of sunflower seeds with the plant growth regulator causes an increase in the area of the leaf surface by 19 %. Over the years of research, the leaves of control plants of hybrid Perseus in the flowering phase contained an average of 8.98 mg / g of dry matter of chlorophylls, which is 31% more than in Alpha and Logos hybrids. It was found that the maximum effect on the index of pigments (Hl./car.) was produced by factor A (58.8 %), while the influence of factors B and C was 1.2 and 1.8%, respectively. In addition, the interaction of factors A and C (24.0 %) was also strong. The AKM plant growth regulator increases the resistance of sunflower plants to abiotic stresses and increases the yield by an average of 31.8 % compared with the control.
Features of photosynthetic activity of sunflower hybrids (Helianthus annuus L.) (F1) depending on the effect of a plant growth regulator under the conditions of the southern Steppe of Ukraine
Keywords: соняшник; фотосинтетична діяльність; регулятор росту рослин; гідротермічні умови; ріст і розвиток рослин; продуктивність; sunflower; photosynthetic activity; plant growth regulator; hydrothermal condi tions; growth and development of plants; productivity